2018
DOI: 10.1007/978-3-319-92486-1_19
|View full text |Cite
|
Sign up to set email alerts
|

The Suitability of Fishes as Models for Studying Appetitive Behavior in Vertebrates

Abstract: Fish have proven to be valuable models in the study of the endocrine control of appetite in response to peripheral signals of energetic and nutritional status. In parallel, a growing body of literature points to the importance of sensory experiences as factors affecting food choice in fish, with a special focus on visual and chemical signals allowing discrimination of potential foods within a 3D environment. Accordingly, waterborne compounds, such as monosaccharides or amino acids, are regarded as the main "ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…These results were confirmed by the second and third trials, with an average of 13 and 11.5 min needed to completely consume the CAU-treated food, respectively, compared to an average of 32 and 30 min in the control groups. Differences in fish voracity were highly significant especially during the last feeding sessions ( Figure 2 , boxes on the right), suggesting that the greater palatability of the CAU-treated food could be associated with a progressive reinforcement of reward memory, possibly involving the endocannabinoid system, which is known to regulate food intake and reward memory in both fish and mammals [ 17 , 18 , 19 ]. This hypothesis is also consistent with the signaling crosstalk between the endocannabinoid system and PPARs [ 20 , 21 ], the main molecular targets of CAU [ 3 ], as well as with previous studies showing that PPARγ agonists cause hyperphagia and consequent weight gain in rodents [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results were confirmed by the second and third trials, with an average of 13 and 11.5 min needed to completely consume the CAU-treated food, respectively, compared to an average of 32 and 30 min in the control groups. Differences in fish voracity were highly significant especially during the last feeding sessions ( Figure 2 , boxes on the right), suggesting that the greater palatability of the CAU-treated food could be associated with a progressive reinforcement of reward memory, possibly involving the endocannabinoid system, which is known to regulate food intake and reward memory in both fish and mammals [ 17 , 18 , 19 ]. This hypothesis is also consistent with the signaling crosstalk between the endocannabinoid system and PPARs [ 20 , 21 ], the main molecular targets of CAU [ 3 ], as well as with previous studies showing that PPARγ agonists cause hyperphagia and consequent weight gain in rodents [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that in fish NPY is synthesized by hypothalamic neurons also releasing Agouti Related Protein (AgRP), an antagonist for the anorexigenic melanocortin receptors [ 22 ]. A plethora of studies have demonstrated the evolutionary conserved orexigenic function of NPY in fish [ 23 , 24 ]. Interestingly, in addition to the pivotal role in regulating food intake, it has been recently demonstrated that NPY is involved in numerous and different functions of fish, such as psychomotor activity [ 25 ], circadian rhythmicity [ 26 ], anxiety-like behaviors [ 27 ], and the recovery of motor function following spinal cord injury [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, galanin, a neuropeptide known to regulate many physiological processes, including feeding and nociception in mammals, displays a wider expression pattern in the larval brain which is restricted to the ventral pallium, lateral hypothalamus, and prethalamus in the adult brain of sea lamprey Petromyzon marinus (Sobrido-Cameán et al). Neuropeptidergic systems controlling food intake behavior are among the most studied in teleost fish, due to the high degree of conservation in vertebrates and the relevant impact in aquaculture (Amodeo et al, 2018). This is indeed the case of Atlantic Salmon (Salmo salar L.), a teleost species providing the unique opportunity for studying vertebrate genome evolution after an autotetraploid whole genome duplication over a period that is long enough to reveal longterm evolutionary patterns, but short enough to give a high-resolution picture of the process (Lien et al, 2016).…”
mentioning
confidence: 99%